Inscribing Senatorial Authority: Epigraphic Epistles and Senatorial Legislation from Constantine I to Theodosius I (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
Imperial epistles (sacrae litterae), which conveyed the emperor’s laws and decrees, were inscribed throughout the empire. Imperial functionaries of the senatorial order in the provinces were the most common recipients of these communications. As a new form of late antique honorific commemoration, honorific inscriptions reproducing imperial letters were set up for the high-ranking members of the aristocracy in Rome and Constantinople. However, the preserved legal inscriptions show that official utterances by high-standing senatorial officials, for which public posting is likely to have taken place, could be also recorded by inscribing in stone in the East and West. This article examines a small dossier of epigraphic epistulae by prefects and governors in the regional administration of the late Roman Empire. It argues that the legal inscriptions of officeholders in the provinces – recorded in the form of epistles in Latin and Greek – testify to the legislative means of the senatorial elite in the imperial service. The inscription in the public archives of the (fragmentary extant) prefectorial and proconsular letters, even if valid within the narrow jurisdiction, served to memorialize the laws issued by the imperial officials, whose authority derived from their appointment by the “sacred” ruler.